Osteoporosis treatment: current drugs and future developments - Chen, Ya-jing; Jia, Li-hua; Han, Tao-hong; Zhao, Zhi-hui; Yang, Jian; Xiao, Jun-ping; Yang, Hong-Jun; Yang, Ke (Frontiers in Pharmacology, 2024)
Osteoporosis is a common systemic metabolic disease characterized by a decrease in bone density and bone mass, destruction of bone tissue microstructure, and increased bone fragility leading to fracture susceptibility. Pharmacological treatment of osteoporosis is the focus of current research, and anti-osteoporosis drugs usually play a role in inhibiting bone resorption, promoting bone formation, and having a dual role.However, most of the drugs have the disadvantages of single target and high toxic and side effects. There are many types of traditional Chinese medicines (TCM), from a wide range of sources and mostly plants. Herbal plants have unique advantages in regulating the relationship between osteoporosis and the immune system, acupuncture therapy has significant therapeutic effects in combination with medicine for osteoporosis. The target cells and specific molecular mechanisms of TCM in preventing and treating osteoporosis have not been fully elucidated. At present, there is a lack of comprehensive understanding of the pathological mechanism of the disease. Therefore, a better understanding of the pathological signaling pathways and key molecules involved in the pathogenesis of osteoporosis is crucial for the design of therapeutic targets and drug development. In this paper, we review the development and current status of anti-osteoporosis drugs currently in clinical application and under development to provide relevant basis and reference for drug prevention and treatment of osteoporosis, with the aim of promoting pharmacological research and new drug development.